KONDISI EKSISTING USAHA MIKRO DAN KECIL KERAJINAN BAHAN ALAM DI KOTA SEMARANG DALAM BERTAHAN MENGHADAPI KRISIS AKIBAT PANDEMI - Berta Bekti Retnawati; Marlon Leong; B Irmawati (STIE Pelita Nusantara Semarang, 2020)
The existing condition due to the crisis during the pandemic period requires micro and small enterprises, including natural handicrafts to survive. This research seeks to portray the situation in the field of adaptive efforts of micro and small enterprises crafting natural raw materials both before a pandemic, during a pandemic and new normal effort in an effort to survive this difficult situation. Research on 20 business actors using convenience sampling method. Micro and small enterprises that can adapt to situations by making innovative efforts and keeping up with market demands are quite resilient. Adaptability can be made through products and marketing methods using e-commerce platforms and social media to approach and expand the target market. On the other hand, micro and small enterprises that are not ready and stuttering in the adaptation process experience difficulties in responding to the changes and challenges that exist. The results of this study are expected to provide an overview of existing conditions and can be input for policy makers in synergy with various parties to continue to strive to maintain micro and small enterprises so that they can exist through the difficult situation of the Covid-19 pandemic